Using Credit Ratings to Improve Water Utility Access to Market Finance in Sub-Saharan Africa - Advani, Rajesh (World Bank, Washington, DC, 2012)
Water and Sanitation Program (WSP) is working to leverage domestic private sector expertise and resources to deliver services that benefit the poor. The aim is to help an estimated 1.5 million poor people gain sustained access to improved water supply and sanitation services and leverage over US$80 million in investments by donors, governments, and the domestic private sector through three main activity lines: building water and sanitation business models for the poor; public-private partnerships in non-traditional markets; and, banking the unbanked water and sanitation providers. Encouraging creditworthy utilities to finance a portion of their investment program using commercial debt will improve the allocation of public funds for investment. Taking steps to address performance issues that hinder access to credit could see significantly more investment in water by the private sector, resulting in improved access in urban areas.